Volunteer Therapeutic Communication for Mount Semeru APG (Hot Cloud Fall) Disaster Survivors - Riesta Ayu Oktarina; Irfan Abdi F; E. Rizky Wulandari; Muhajir Sulthonul Aziz; Renny Candradewi Puspitarini (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2025)
Abstract The potential for disasters in Indonesia is still quite high, especially in disaster potential areas, on December 4, 2021, the Mount Semeru APG (Hot Clouds Fall) disaster occurred which resulted in 48 deaths of people and damage to several areas around Mount Semeru which required 10,158 people to evacuate. The Mount Semeru APG disaster has received treatment from the government and social institutions. One of them is Laznas LMI which also assigns volunteers to go to disaster areas. In addition to searching for missing victims, volunteers also interact directly with survivors, researchers are interested in examining how the communication carried out by volunteers during post-disaster conditions with volunteers' therapeutic communication to the survivors, Therapeutic communication has 4 stages, namely the pre-interaction stage, the orientation stage, the work stage and the termination stage. This study uses a qualitative descriptive method, the research informants are the Head of the Central LMI Emergency Response Section and representatives of the LMI Volunteers in Blitar City who also participated in the disaster location. The results of obtaining data from informants, residents still feel comfortable with the situation that occurs and are still burdensome for livelihoods. Keywords: Therapeutic Communication, Volunteers, APG Semeru Disaster